Linked-color imaging versus high definition white-light endoscopy for evaluation of post-polypectomy scars of nonpedunculated lesions: LCI-Scar study - Ortiz, Oswaldo; Daca-Alvarez, Maria; Rivero-Sánchez, Liseth; Saez De Gordoa, Karmele; Moreira, Rebeca; Cuatrecasas, Miriam; Balaguer, Francesc; Pellisé, Maria (Endoscopy, 2023)
Background Detection and treatment of recurrence after piecemeal endoscopic mucosal resection of nonpedunculated colorectal polyps are crucial for avoidance of post-colonoscopy cancer. Linked-color imaging (LCI) has demonstrated improved polyp detection but has never been assessed for evaluation of post-polypectomy scars. Our aim was to compare sensitivity and negative predictive value (NPV) between LCI and white-light endoscopy (WLE) for detection of post-polypectomy recurrence.Methods Patients undergoing surveillance colonoscopy after resection of lesions ≥15 mm were included in this prospective, single-center, randomized, crossover study. Each post-polypectomy scar underwent two examinations, one with LCI and the other with WLE, performed by two blinded endoscopists. Blue-light imaging (BLI) was then applied. A diagnosis of recurrence with a level of confidence was made for each modality and histopathology was the gold standard.Results 129 patients with 173 scars were included. Baseline patient, lesion, and procedural characteristics were similar in both arms. Recurrence was detected in 56/173 (32.4%), with 27/56 (48.2%) adenomas and 29/56 (51.8%) serrated lesions. LCI had greater sensitivity (96.4% [95%CI 87.8%–99.5%]) versus WLE (89.3% [95%CI 78.1%–95.9%]) and greater NPV (98.1% [95%CI 93.4%–99.8%] versus 94.6% [95%CI 88.7%–98.0%]). Paired concordance between modalities was 96.0%. In discordant cases, LCI identified four true-positive cases not detected by WLE and reclassified one false-positive of WLE. WLE reclassified two false positives of LCI without any increase in recurrence detection.Conclusions LCI was highly accurate and had greater ability than WLE to rule out recurrence on post-polypectomy scars after resection of large polyps.